Poor participation : fighting the wars on poverty and impoverished citizenship - Bryer, Thomas A., 1978-; Prysmakova-Rivera, Sofia (Democratic dilemmas and policy responsiveness., 2018)
This book presents a philosophy of and strategies for a war on poverty and impoverished citizenship for the twenty-first century. It focuses on the United States, with comparison to some international experiences, and considers poverty in all its forms-subsistence, agency, and status.